Inflammation and Erythropoiesis-Stimulating Agent Response in Hemodialysis Patients: A Self-matched Longitudinal Study of Anemia Management in the Dialysis Outcomes and Practice Patterns Study (DOPPS) - Karaboyas, Angelo (Kidney Med, 2020)
RATIONALE & OBJECTIVE: Previous studies of inflammation and anemia management in hemodialysis (HD) patients may be biased due to patient differences. We used a self-matched longitudinal design to test whether new inflammation, defined as an acute increase in C-reactive protein (CRP) level, reduces hemoglobin response to erythropoiesis-stimulating agent (ESA) treatment. STUDY DESIGN: Self-matched longitudinal design. SETTING & PARTICIPANTS: 3,568 new inflammation events, defined as CRP level > 10 mg/L following a 3-month period with CRP level ≤ 5 mg/L, were identified from 12,389 HD patients in the Dialysis Outcomes and Practice Patterns Study (DOPPS) phases 4 to 6 (2009-2018) in 10 countries in which CRP is routinely measured. PREDICTOR: “After” (vs “before”) observing a high CRP level. OUTCOMES: Within-patient changes in hemoglobin level, ESA dose, and ESA hyporesponsiveness (hemoglobin < 10 g/dL and ESA dose > 6,000 [Japan] or >8,000 [Europe] U/wk). ANALYTICAL APPROACH: Linear mixed models and modified Poisson regression. RESULTS: Comparing before with after periods, mean hemoglobin level decreased from 11.2 to 10.9 g/dL (adjusted mean change, −0.26 g/dL), while mean ESA dose increased from 6,320 to 6,960 U/wk (adjusted relative change, 8.4%). The prevalence of ESA hyporesponsiveness increased from 7.6% to 12.3%. Both the unadjusted and adjusted prevalence ratios of ESA hyporesponsiveness were 1.68 (95% CI, 1.48-1.91). These associations were consistent in sensitivity analyses varying CRP thresholds and were stronger when the CRP level increase was sustained over the 3-month after period. LIMITATIONS: Residual confounding by unmeasured time-varying risk factors for ESA hyporesponsiveness. CONCLUSIONS: In the 3 months after HD patients experienced an increase in CRP levels, hemoglobin levels declined quickly, ESA doses increased, and the prevalence of ESA hyporesponsiveness increased appreciably. Routine CRP measurement could identify inflammation as a cause of worsened anemia. In turn, these findings speak to a potentially important role for anemia therapies that are less susceptible to the effects of inflammation.